Memanfaatkan Alat Media untuk Meningkatkan Pendidikan Bahasa Arab di Madrasah Ibtidaiyyah (MI) - Hilliatus Sa'adah; Syifaul Adhimah (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2024)
Teaching Arabic at the elementary school level, especially at MI Ar-Rahman, plays a crucial role in forming students' foundational linguistic and cultural understanding. However, challenges such as the limited availability of interactive teaching materials and innovative teaching methods often make the learning process monotonous and less effective. This research examines the use of media tools such as learning applications, educational videos, and interactive games to enhance Arabic education in the 3rd grade at MI Ar-Rahman.The results of the study indicate that the use of media tools can significantly improve students' learning motivation and outcomes. Media tools help deliver material in a more visual and interactive manner, catering to various student learning styles. Teachers can also develop more creative and effective teaching methods. This research suggests that other MIs should consider using media tools to create a more dynamic and effective learning environment, ultimately enhancing students' Arabic language competence.